Existence of the Category DTC₂(K) Equivalent to the Given Category KAC₂ - Han, S.-E. (Український математичний журнал, 2015)
For a given category KAC₂, the present paper deals with an existence problem of the category DTC₂(k) which is equivalent to KAC₂, where DTC₂(k) is the category whose objects are simple closed k-curves with even number l of elements in Zⁿ, l ≠ 6 and morphisms are (digitally) k-continuous maps, and KAC₂ is the category whose objects are simple closed A-curves and morphisms are A-maps. To address this issue, the paper starts with the category, denoted by KAC₁, whose objects are connected nD Khalimsky topological subspaces with Khalimsky adjacency and morphisms are A-maps in [Han S. E., Sostak A. A compression of digital images derived from a Khalimsky topological structure // Comput. and Appl. Math. – 2013. – 32. – P. 521 – 536]. Based on this approach, in KAC₁ the paper proposes the notions of an A-homotopy and an A-homotopy equivalence, and classifies spaces in KAC₁ or KAC₂ in terms of an A-homotopy equivalence. Finally, the paper proves that for a given category KAC₂ there is DTC₂(k) which is equivalent to KAC₂. Для заданої категорiї KAC₂ вивчено проблему iснування категорiї DTC₂(k), що еквiвалентна KAC₂, де DTC₂(k) — категорiя, об’єктами якої є простi замкненi k-кривi з парним числом l, l ≠ 6, елементiв в Zⁿ, а морфiзмами — (цифрово) k-неперервнi вiдображення, тодi як KAC₂ — категорiя, об’єктами якої є простi замкненi A-кривi, а морфiзми є A-вiдображеннями. Наш виклад ми починаємо з категорiї, що позначена KAC₁, об’єктами якої є nD зв’язнi топологiчнi пiдпростори Халiмського з сумiжнiстю Халiмського, а морфiзми є A-вiдображеннями, що визначенi в [Han S. E., Sostak A. A compression of digital images derived from a Khalimsky topological structure // Comput. and Appl. Math. – 2013. – 32. – P. 521 – 536]. На основi запропонованого пiдходу в категорiї KAC₁ введено поняття A-гомотопiї та A-гомотопiчної еквiвалентностi, а простори з KAC₁ або KAC₂ класифiковано в термiнах A-гомотопiчної еквiвалентностi. Насамкiнець доведено, що для заданої категорiї KAC₂ iснує DTC₂(k), еквiвалентнa KAC₂.